HAK MENDAHULU NEGARA ATAS UTANG PAJAK UNTUK WAJIB PAJAK DINYATAKAN PAILIT DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 28 TAHUN 2007 TENTANG KETENTUAN UMUM DAN TATA CARA PERPAJAKAN - NIRWANA DEWI HARAHAP (LP2MTBM MAKARIOZ, 2022)
Taxes are the largest state revenue in Indonesia aimed at the needs of the state for the greatest prosperity of the people. Given the importance of tax revenue for the prosperity of the Indonesian people, the government must optimize tax revenues, both from the regulatory and implementation aspects. Article 21 paragraph (3) letter a of the Law of the Republic of Indonesia Number 28 of 2007 concerning the Third Amendment to Law Number 6 of 1983 concerning General Provisions and Tax Procedures has explicitly regulated the state's prior rights in obtaining payment of tax debts from bankrupt debtors , where the curator is prohibited from distributing the assets of the Taxpayer (Debtor) in bankruptcy to other creditors before using the assets to pay the taxpayer's tax debt.